Agalma clausi (Bedot, 1888) (Siphonophora: Physonectae)—complementary description with notes on species distribution and ecology - Mańko, Maciej K.; Pugh, Philip R. (Zootaxa, 2018)
Siphonophores are colonial hydrozoans, which in spite of often growing to great lengths are an inconspicuous and understudied component of pelagic ecosystems. Although they are widely distributed, many species have rarely been collected, or often been misidentified so their taxonomy still requires some clarification. Here we redescribe one such species, Agalma clausi Bedot, 1888, supplementing information on its morphology, ecology and distribution based on the material collected in the tropical sector of the Atlantic Ocean and adjacent seas. We also provide comments on the probable status of another Agalma species, A. haeckeli Bigelow, 1911.